THE SHORT-TERM AGRICULTUAL LENDING OF ACCESS TO THE OPTIMAL PRODUCTION VOLUME FOR WHEAT FARMERS IN NINEVEH GOVERNORATE - Hanaa Dawood (Mesopotamia Journal of Agriculture)
ABSTRACT The research aims to quantify the impact of short-term loans in determining amazed optimal output achieved at the lowest point of the average total costs at the farm level. The search started from hypothesis that small producers of wheat liable variable capital necessary for expansion in investment the variable elements production to arrive rational stage of production. And comes the role of short-term borrowing and one of the tools to help producers to achieve this. They designed a questionnaire included a series of questions related to various production costs and what can leave over the farmer from the production requirements in case of the lack of capital and also he does not borrowed The sample included research (50) farms from farmers wheat crop in the area of Qush. One of the most important findings of the research show that the productivity of one ton of the wheat crop in the case of farmer do not borrowing was 558.622 kg while the productivity of one ton in the case of farmer borrowing was 1091 kg. It included some of the recommendations.